The reflexive modernization of Australian universities - Pick, David (Carfax Publishing, 2004)
The profound changes occurring in Australian higher education are viewed here in the context of the social, cultural, political and economic effects of globalization. Particular attention is paid to providing a theoretical foundation for understanding these effects using the reflexive modernization perspective. Highlighted are some of the challenges facing universities in Australia brought about by the corrosive influences of individualization and risk. This paper includes a call for a more critical and intentional approach to higher education policy and management.